Immature platelet values indicate impaired megakaryopoietic activity in neonatal early-onset thrombocytopenia - Cremer, Malte; Weimann, Andreas; Hammer, Hannes; Bührer, Christoph; Dame, Christof (Thrombosis and Haemostasis, 2010)
Newly released platelets, referred to as immature platelets, can be reliably quantified based on their RNA content by flow cytometry in an automated blood analyser. The absolute number of immature platelets (IPF#) and the immature platelet fraction (IPF%) reflect megakaryopoietic activity. We aimed to analyse the implication of these parameters in analysing the pathomechanism of early-onset neonatal thrombocytopenia. Platelet counts and IPF were determined at day 1 to 3 (d1 to d3) in 857 neonates admitted to intensive care. In thrombocytopenic patients (platelet counts<150 x 109/l, n=129), IPF# was significantly lower (8.5 ± 2.7 x 109/l), than in non-thrombocytopenic neonates (9.5 ± 3.6 x 109/l, n=682, p<0.05). IPF% was significantly higher in thrombocytopenic (9.3 ± 7.9%) vs. non-thrombocytopenic neonates (4.1 ± 1.8%, p<0.001). While neonates with early-onset infection (n=134) had lower platelet counts (199 ± 75 x 109/l) compared to controls (230 ± 68 x 109/l, n=574, p<0.01), there were no differences in IPF# or IPF%. Likewise, “small for gestational age” infants (SGA, n=149) had lower platelet counts at d1 (199 ± 75 x 109/l, p<0.001) than controls, but no differences in IPF. A trend towards lower IPF# was detected if SGA infants with platelet counts <100 x 109/l (5.4 ± 3.9 x 109/l, n=11) and thrombocytopenic neonates with infection (9.9 ± 7.3 x 109/l, n=10, p=0.11) were compared. The evaluation of IPF# indicates that thrombocytopenia in neonates is likely due to a combination of increased platelet consumption and inadequate megakaryopoietic response by the neonatal bone marrow. Furthermore, SGA neonates with moderate and severe thrombocytopenia might have a pronounced suppression of megakaryopoiesis compared to neonates with infection.
Keywords: Immature platelet count; reticulated platelets